A broadband frequency-tunable dynamic absorber for the vibration control of structures. (September 2016) - Komatsuzaki, T; Inoue, T; Terashima, O
Abstract: A passive-type dynamic vibration absorber (DVA) is basically a mass-spring system that suppresses the vibration of a structure at a particular frequency. Since the natural frequency of the DVA is usually tuned to a frequency of particular excitation, the DVA is especially effective when the excitation frequency is close to the natural frequency of the structure. Fixing the physical properties of the DVA limits the application to a narrowband, harmonically excited vibration problem. A frequency-tunable DVA that can modulate its stiffness provides adaptability to the vibration control device against non-stationary disturbances. In this paper, we suggest a broadband frequency-tunable DVA whose natural frequency can be extended by 300% to the nominal value using the magnetorheological elastomers (MREs). The frequency adjustability of the proposed absorber is first shown. The real-time vibration control performance of the frequency-tunable absorber for an acoustically excited plate having multiple resonant peaks is then evaluated. Investigations show that the vibration of the structure can be effectively reduced with an improved performance by the DVA in comparison to the conventional passive- type absorber.